Changes in microbial community during the factory production of sweet dumplings from glutinous rice determined by high-throughput sequencing analysis. (15th April 2023) - Suo, Biao; Dong, Zijie; Huang, Yangyang; Guan, Peng; Wang, Xiaojie; Fan, Huiping; Huang, Zhongmin; Ai, Zhilu
Abstract: To study the source of microorganisms in sweet dumplings factory produced from glutinous rice, samples including raw materials, semifinished and products, and surface of facilities, were collected from a local factory production line. Viable cell count showed that the presence of more than 4 CFU/cm 2 of Staphylococcus aureus and Bacillus cereus, lactic acid bacteria and total plate count in the soaking and milling tank, milling pipeline, and temporary storage tank. The most significant increase in microbial counts were observed in the soaking and milling procedure of raw materials. Thereafter, five samples were subjected to high-throughput sequencing (HTS) analysis, including two raw materials japonica (RJ) and indica (RI) flours, two semifinished products milled rice milk (MR) and mixed dough (MD), and one final product sweet dumpling (SD). The predominant genera of bacteria in SD were Leuconostoc, Chryseobacterium and Lactococcus, and the predominant fungi were Apiotrichum, Aspergillus and Geotrichum . The rice flour added in MR significantly affected the bacterial community of sweet dumpling product, but this influence was not shown at the fungal level. The results showed that the combination of HTS and viable cell count can effectively analyse the changes in microbial load and diversity during the production of sweet dumplings. Highlights: The microbiota in the production chain of a sweet dumplings factory was analyzed for the first time. The rice soaking and milling process contributes to the microbial growth. The added glutinous rice flour is the main cause of changes in the bacterial structure of the products. Sweet dumplings are susceptible to microbial cross-contamination in pipes and containers. The microbial critical control points of the sweet dumplings production chain were clarified.